2020
DOI: 10.21873/invivo.12054
|View full text |Cite
|
Sign up to set email alerts
|

ERK/AKT Inactivation and Apoptosis Induction Associate With Quetiapine-inhibited Cell Survival and Invasion in Hepatocellular Carcinoma Cells

Abstract: Background/Aim: Quetiapine, an atypical antipsychotic, has been encountered as a potential protective agent to suppress various types of tumor growth. However, the inhibitory mechanism of quetiapine in hepatocellular carcinoma (HCC) still remains unclear. The purpose of present study was to investigate the inhibitory mechanism of quetiapine on cell survival and invasion in HCC. Materials and Methods: Changes of apoptotic signaling, migration/invasion ability, and signaling transduction involved in cell surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…For subG1 analysis, the harvested cells were fixed by 70% ethanol overnight at −20 °C and stained by a PI/RNase solution (cat: 550625, BD Biosciences). The fluoresce signal from the cells was detected and quantified by NovoCyte flow cytometry and the NovoExpress ® software (Agilent Technologies Inc., Santa Clara, CA, USA) [ 15 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For subG1 analysis, the harvested cells were fixed by 70% ethanol overnight at −20 °C and stained by a PI/RNase solution (cat: 550625, BD Biosciences). The fluoresce signal from the cells was detected and quantified by NovoCyte flow cytometry and the NovoExpress ® software (Agilent Technologies Inc., Santa Clara, CA, USA) [ 15 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Hep3B and SK-Hep1 cells (5 × 10 5 ) were seeded in 6-well plates overnight and treated with 50 μM magnolol, 10 μM regorafenib, and a combination for 48 h. The viable cells counted by trypan blue were then collected for transwell migration and invasion analysis, as previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the glioma cells that developed resistance in the combination of quetiapine and irradiation-expressed genes involved in cholesterol synthesis, and the addition of atorvastatin, a 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMG-CoA) inhibitor, enhanced the efficacy of quetiapine [ 130 ]. Moreover, epidemiological studies have shown that quetiapine reduces the risk of hepatocellular carcinoma development in patients with schizophrenia [ 131 ], while according to Lee et al, quetiapine inhibited cell proliferation and migration of Hep1 and Hep3B HCC cancer cell lines and induced their apoptosis via activation of intrinsic and extrinsic apoptotic pathways and simultaneous reduction of expression of anti-apoptotic proteins such as XIAP and survivin via inhibition of the ERK/AKT signaling pathway [ 132 ].…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%
“…Furthermore, cell and animal models have been used to study the anti‐cancer property of antipsychotics. Antipsychotic has been shown to possess potent anti‐cancer properties which are involved in suppression of tumor growth, invasion, metastasis, and reversion of chemoresistance 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotics such as olanzapine (3 mg/kg/day) and quetiapine (25 mg/kg/day) have been found to correlate with increased risk of liver cancer and thyroid adenoma in mice 11 . Previous studies indicated that suppression of extracellular signal‐regulated kinases (ERK)/protein kinase B (AKT) signaling and induction of apoptosis were associated with quetiapine‐inhibited cell survival and invasion in HCC in vitro 4 . However, whether quetiapine influences the progression of HCC in vivo has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%